Characterization, tissue distribution of resistin gene and the effect of fasting and refeeding on resistin mRNA expression in Siberian sturgeon (Acipenser baerii). Issue 2 (21st June 2020) - Tang, Ni; Liu, Yanlin; Tian, Zhengzhi; Xu, Shaoqi; Wang, Mei; Chen, Hu; Wang, Bin; Li, Ya; Wang, Yan; Yang, Song; Zhao, Liulan; Chen, Defang; et al.
Abstract: Resistin as an adipokine identified from rodents in 2001 is involved in many biological processes. However, little is known about this gene in fish. We cloned Siberian sturgeon ( Acipenser baerii ) resistin cDNA of 795 base pairs, encoding 107 amino acids, which showed 38–40% identity to human and rodents. Real‐time quantitative PCR showed that the resistin gene was widely distributed in tissues of Siberian sturgeon, with the highest expression in liver. After fasting for 1, 3, 6 and 10 days, the expression of the resistin gene in the liver of Siberian sturgeon decreased significantly, and after refeeding on the 10 days of fasting the resistin mRNA expression increased rapidly, suggesting that resistin may play an important role in liver in response to starvation. Taken together, these results suggest that resistin may be involved in the regulation of energy homeostasis in liver.